Backscattering of Ultrasonic Waves as the Basis of the Method of Control of Structure and Physicо-Mechanical Properties of Cast Irons - A. R. Baev; N. V. Levkovich; E. P. Babuk; M. V. Asadchaya (Приборы и методы измерений)
Increasing the reliability of control of cast iron structure and its physical and mechanical characteristics is an important scientific and technical task of the machine-building industry. The paper studies the possibilities of controlling the structure of cast irons using structural noise created by ultrasonic scattering on graphite inclusions of different shapes. The subject of the present studies was such characteristics of structural noise as amplitude-temporal A(t) and as root mean square value of the amplitude of the ultrasonic waves backscattering field AN, compared with the data on ultrasonic velocity and strength or tensile strength of cast iron samples. As a result of the studies, a significant difference between the amplitude parameters of the AN structural noise obtained for samples with different shapes of graphite inclusions at 5 MHz was revealed for the first time. So, for example, for samples of gray cast iron (Russian: СЧ10, СЧ15, СЧ20, СЧ25), having predominantly plate-like form of graphite inclusions, the value of AN on 14–15 dB exceeds that measured in high-strength specimens of the cast iron with the prevailing form of spherical graphite inclusions ВЧ50 (Russian), etc. At the same time growth of longitudinal ultrasonic velocity amounted to 20–25 %. The method of rejection of gray cast iron from high-strength cast iron according to the data of amplitude parameters of structural noise AN at unilateral and local sounding of the object without using an additional reference signal reflected from its oppositional wall is suggested.